APPLICATIONS OF ELECTROCHEMICAL SENSORS IN THE MONITORING OF CHEMICAL SPECIES IN THE ENVIRONMENT: AN ANALYSIS OF IMPACT - Mancilla G., Juan C. (Journal of the Chilean Chemical Society, 2024)
In recent years, electrochemical sensors have garnered significant attention in the environmental field due to their potential to offer effective solutions for addressing the environmental challenges our planet faces, particularly in proactive environmental preservation. A particular interest has been focused on the development of electrochemical sensors due to their restricted sample volume and the potential for system miniaturization, enabling portability. Taking these aspects into consideration, this review centers on the utilization of electrochemical electrodes to acquire relevant chemical information pertaining to environmental issues. Furthermore, it will analyze how the use of nanotechnology has provided new substrate alternatives for the determination of chemically significant species in the environment. Finally, the challenges and future prospects in this field are discussed.